Analisis Tingkat Suku Bunga, Rasio Profitabilitas dan Harga Saham pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) - Afriza Amir; Muhammad Arief; Yulizar Erliza (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2022)
The presence of a capital market in Indonesia is one alternative for the investor to make an investment. The most widely used investment by investors is in the form of stock. Analysis of interest rate and profitability ratios that include calculations and interpretations of stock price developments to support economic growth. This research is conducted to analyze interest rates, profitability ratios, and stock prices of mining companies listed on the Indonesia Stock Exchange. This research is a type of quantitative descriptive research. The population in this study was 43 mining companies listed on the Indonesian Stock Exchange. The purposive sampling method was used in determining 5 companies the samples. This study indicated that there is an impact of interest rates and profitability ratios on stock prices.